Paper and light : luminous drawings - Brooks, Julian, 1969-; Sullivan, Michelle (Conservator); J. Paul Getty Museum (Los Angeles : J. Paul Getty Museum, 2024)
"Discusses the history of extraordinary light effects on the surface of and through paper in drawings from the Renaissance to today"--
"This publication is issued on the occasion of the exhibition Paper and Light: Luminous Drawings, on view at the J. Paul Getty Museum at the Getty Center, Los Angeles, from October 15, 2024, to January 19, 2025"--Colophon.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Shades and shadows in art -- Exhibitions; Light in art -- Exhibitions; Drawing, European -- Exhibitions; Drawing -- Technique -- Exhibitions; Paper -- Europe -- Exhibitions; Ombres dans l'art -- Expositions; Lumière dans l'art -- Expositions; Dessin européen -- Expositions; Dessin -- Technique -- Expositions; ART / General; Electronic books